Business Development - Sofyan Mufti Prasetiyo; Ali Basir; Andini; Muhamad Fathan (CV. Multi Kreasi Media, 2022)
Business development is a position to identify business development in its development, this includes the provision of new innovations that are very encouraging for business development in the future. A business development manager is a high-level position in the business development of a company and has a better understanding of the business being run by the company, starting from the targets, products and strategies to be carried out. This position is different from the position as sales development, but both of them can give each other their best ideas to improve the company's quality in the eyes of other competitors engaged in similar fields.